2008
DOI: 10.1299/jtst.3.112
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Heat Transfer Mechanism in Turbulent Supercritical CO2 Channel Flow

Abstract: Direct numerical simulation (DNS) of supercritical CO 2 turbulent channel flow has been performed to investigate the heat transfer mechanism of supercritical fluid. In the present DNS, full compressible Navier-Stokes equations and Peng-Robison state equation are solved. Due to effects of the mean density variation in the wall normal direction, mean velocity in the cooling region becomes high compared with that in the heating region. The mean width between high-and low-speed streaks near the wall decreases in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…We remark that the variable-property algorithm employed in this work is similar to those developed by Bae, Yoo & Choi (2005), Li et al (2008), Sewall & Tafti (2008) and Kang, Iaccarino & Ham (2009). In all of these cases the viscosity, density and thermal conductivity vary with temperature.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We remark that the variable-property algorithm employed in this work is similar to those developed by Bae, Yoo & Choi (2005), Li et al (2008), Sewall & Tafti (2008) and Kang, Iaccarino & Ham (2009). In all of these cases the viscosity, density and thermal conductivity vary with temperature.…”
Section: Introductionmentioning
confidence: 81%
“…Kang et al (2009) considered conjugate heat transfer around a cylinder in a channel heated from below where the working fluid is water, yet its dependency upon temperature is implemented using tabulated data. Bae et al (2005) performed DNSs of turbulent CO 2 fluid at supercritical pressure in heated vertical tubes with low-Mach-number approximation and considering buoyancy effects, whereas Li et al (2008) analysed a similar problem (supercritical CO 2 turbulent flow) in a different geometry (channel flow) and with a fully compressible approach (albeit neglecting buoyancy effects).…”
Section: Introductionmentioning
confidence: 99%
“…The streamwise extent of the computational domain is deemed sufficient for the present study as several authors have observed that heated turbulent flows with supercritical working fluids are dominantly affected by nearwall flow phenomena. 25,27,28,40 To ensure that the coherent flow structures are self sustaining, the span of the computational domain must adhere to L z + > 220. 39 The domain span of L z + > 740 (L z = 3.2δ) for the present study is therefore quite conservative.…”
Section: B Computational Domainsmentioning
confidence: 99%
“…The validity of using shorter domains and hence not resolving the largest scales is discussed in detail by Jimenez et al (1999Jimenez et al ( , 1991. (Azih et al, 2012;Bae et al, 2008;Li et al, 2007;Bae et al, 2005). To ensure that the coherent flow structures are self sustaining, the span of the computational domain must adhere to L z + >220 (Jimenez & Moin, 1991).…”
Section: Computational Domainsmentioning
confidence: 99%
“…This velocity profile is specified at the inflow boundary and is used to initialize the computational domain. In Equation A-1, the origin is located at the bottom surface as illustrated in Figure A- phenomena (Azih et al, 2012;Bae et al, 2008;Li et al, 2007). Therefore, the computational domain must be sufficiently long to accurately capture the transient flow structures developing in the near-wall region.…”
Section: A12 Computational Domains Boundary Conditions and Initialmentioning
confidence: 99%